Political Strategy of the National Awakening Party (PKB) in the 2019 Legislative Election in Pandeglang Regency: A Study of Irvan Nugraha’s Victory in Mandalawangi District - Ariyan, Said; Andreansyah (Lenggogeni Data Publishing, 2025)
This study aims to analyze the political strategy of the National Awakening Party (PKB) during the 2019 Legislative Election in Pandeglang Regency, focusing on the case of Irvan Nugraha’s electoral victory in Mandalawangi District. Irvan Nugraha was the only legislative candidate from Mandalawangi who succeeded in being elected as a member of the Pandeglang Regional House of Representatives (DPRD) for the 2019–2024 period, obtaining 1,685 votes. This research employed a qualitative approach using literature studies, interviews, and documentation. The data were analyzed through collection, presentation, and conclusion stages. The findings indicate that Irvan Nugraha’s political strategies included presence politics, the development of popularity and electability, network building, financial resource management, political marketing, target segmentation, and positive political imaging. The key supporting factors were strong volunteer mobilization and the influential reputation of his father and father-in-law, which enhanced his sociopolitical legitimacy. The researcher recommends maintaining public trust and relationships with religious and traditional leaders by consistently advocating for community aspirations in the governmental sphere.